Active transport research priorities for Australia. (March 2022) - Beck, Ben; Thorpe, Amelia; Timperio, Anna; Giles-Corti, Billie; William, Carmel; de Leeuw, Evelyne; Christian, Hayley; Corben, Kirstan; Stevenson, Mark; Backhouse, Melissa; Ivers, Rebecca; Hayek, Rema; et al.
Abstract: Background: To advance active transport, robust policy-relevant evidence is needed to understand how to change behaviour and to support decision-making by policy makers and practitioners. Currently, however, priority research questions that are most critical for advancing active transport have not been identified. To this end, we aimed to inform an active transport research priority agenda for Australia to guide research, funding, policy making and practice to enhance active transport. Methods: We designed and conducted a novel priority setting exercise to identify and set research priorities for the advancement of active transport in Australia. The process consisted of three phases: 1) generation and collection of research questions from a diverse reference group consisting of experts and key members representing academia, government, private and not-for-profit organisations (n = 259 respondents); 2) thematic analysis and consolidation of research questions to a final list of 50 questions; and 3) prioritisation of research questions by the reference group (n = 140 respondents). Results: The top ranked questions included the evidence to support policy changes to increase active transport, identifying and overcoming community resistance to active transport infrastructure, road space re-allocation and lower urban speed limits, evidence on the needs of children, enhanced governance and funding, and improving how the benefits of active transport are best measured and communicated. Conclusions: To our knowledge, this is the first priority setting exercise in active transport globally. The identified research priorities can be used to identify new policy-relevant areas of research, contribute to the active transport research agenda in Australia and guide research funding. Focusing on these research priorities will address stakeholder and academic priorities and provide the evidence required to support the advancement of active transport in Australia. Future research could use the same approach to identify research priorities in other countries. Highlights: We conducted a priority setting exercise to set active transport research priorities. The priorities represent the consensus of a diversity of active transport experts. Focusing on these priorities will support the advancement of active transport.